Humanist Education at Anand Niketan: An Intercultural Exchange - Parul Malik; Anita Rampal (Voices of Teachers and Teacher Educators, 2025)
Learning which is meaningful, relatable to one’s life and surroundings, and exemplifies a sense of community, togetherness and love is part of students’ schooling experience at the Gandhian school Anand Niketan in Sevagram. This paper emerges from an intercultural exchange project on Education for Sustainable Development (ESD), which a group of Swiss student-teachers and teacher educators, along with a professor and research scholars from Delhi University, engaged in at Anand Niketan. The theme for this academic trip was ‘Cotton’ – to understand the concept of ESD in the local, rural Indian context, while juxtaposed with and in contrast to urban, industrialised, and Euro-centric Western contexts. In this paper, we explore the humanist ethos of this school at Sevagram detailed through curricular examples of collaborative, multidisciplinary crafts-based learning and productive labour, and make critical reflections on the experience of intercultural exchange itself.